The pragmatic turn in law : inference and interpretation in legal discourse - Giltrow, Janet; Stein, Dieter, 1946- (Mouton series in pragmatics ;, 2017)
This collection of contributions from both linguists and lawyers brings a pragmatic perspective to the linguistic basis for legal meaning and for finding a norm by which to decide a case. That is, it turns from notions of linguistic meaning as residing in the text, as literal meaning waiting to be dug out, to focus instead on how readers infer pragmatic meaning, and on the kinds of inferencing that characterise legal discourse.